Spatial Distribution, Health Risk Assessment and Survey of Fluoride Pollution Source with GIS in Drinking Water: A Case Study, Abarkouh, Iran - Reza Ali Fallahzadeh; Davood Ghadirian (Journal of Environmental Health and Sustainable Development, 2018)
Introduction: Exposure to high concentrations of fluoride in drinking water can negatively affect lung, liver and kidney tissues, and cause skeleton pain; however, lack of fluoride can cause tooth decay and bone problems. Materials and Methods: In this study, the concentration of fluoride was investigated and its spatial distribution was carried out with Arc GIS software in underground water of Abarkouh aquifer. The health risk assessment, type of pollution distribution and its source was investigated using Moran's index. Results: The average concentration of fluoride in 21 wells was 0.623 ± 0.296 mg/L which in 47.61% were less than the minimum concentration standard range set by the WHO guidelines. The Moran's index for fluoride concentration in the study area was 0.653 and given the z-score of 4.117. There is less than 1% likelihood that this clustered pattern could be the result of a random chance. Conclusion: According to the results, Non-carcinogenic risk indicates a high risk for children (HQ = 1.03E0). The source of pollution is close to well No. 15. Investigating the study area and eliminating the pollution source is effective in decreasing the fluoride concentration of water and can reduce the health risk for children.